Synthesis and Antibacterial Activity of 6-Amino-2-[(E)-2-(4-hydroxy-3-methoxyphenyl)ethenyl]-3,4-dihydroquinazolin-4-one and its Intermediate Compounds - Arrahman, A.; Hayun; Suryadi, H. (Asian Journal of Chemistry, 2015)
6-Amino-2-[(E)-2-(4-hydroxy-3-methoxyphenyl)ethenyl]-3,4-dihydroquinazolin-4-one was synthesized in four steps. The synthesized product from each step was purified by washing and recrystallization. Purity testing was performed by examining the melting range and by thin layer chromatography. The molecular mass of the synthesized compound was determined using LC-MS. Structure of synthesized compound was elucidated using UV-visible, FT-IR, 1H NMR, 13C NMR, COSY, HMQC and HMBC. Screening for antibacterial activity was performed against Staphylococcus aureus ATCC 25923, Salmonella typhimurium ATCC 14028 and Escherichia coli ATCC 25922. The results indicated that the titled compound had been successfully synthesized and purified. The structure of desired compound was confirmed based on structural elucidation analysis. The result of testing the titled compound for the antibacterial activity was negative.